Protective Effect of Glycyrrhizin, a Direct HMGB1 Inhibitor, on Focal Cerebral Ischemia/Reperfusion-Induced Inflammation, Oxidative Stress, and Apoptosis in Rats - Gong, Gu (Public Library of Science, 2014)
AIM: Glycyrrhizin (GL) has been reported to protect against ischemia and reperfusion (I/R)-induced injury by inhibiting the cytokine activity of high mobility group box 1 (HMGB1). In the present study, the protective effects of GL against I/R injury, as well as the related molecular mechanisms, were investigated in rat brains. METHODS: Focal cerebral I/R injury was induced by intraluminal filamentous occlusion of the middle cerebral artery (MCA) in Male Sprague-Dawley rats. GL alone or GL and rHMGB1 were administered intravenously at the time of reperfusion. Serum levels of HMGB1 and inflammatory mediators were quantified via enzyme-linked immunosorbent assay (ELISA). Histopathological examination, immunofluorescence, RT-PCR and western blotting analyses were performed to investigate the protective and anti-apoptotic effects and related molecular mechanisms of GL against I/R injury in rat brains. RESULTS: Pre-treatment with GL significantly reduced infarct volume and improved the accompanying neurological deficits in locomotor function. The release of HMGB1 from the cerebral cortex into the serum was inhibited by GL administration. Moreover, pre-treatment with GL alleviated apoptotic injury resulting from cerebral I/R through the inhibition of cytochrome C release and caspase 3 activity. The expression levels of inflammation- and oxidative stress-related molecules including TNF-α, iNOS, IL-1β, and IL-6, which were over-expressed in I/R, were decreased by GL. P38 and P-JNK signalling were involved in this process. All of the protective effects of GL could be reversed by rHMGB1 administration. CONCLUSIONS: GL has a protective effect on ischemia-reperfusion injury in rat brains through the inhibition of inflammation, oxidative stress and apoptotic injury by antagonising the cytokine activity of HMGB1.